The external rhythm in the poem and the production of meaning : A phonetic reading of the Lamia of Alshanfara - Alloul, Ilhem (Journal of Human Sciences, 2022)
The research deals with a reading of Al sfanfara s poem as an important document to learn about the wretch s poetry and their thought, and because it reflects the depth of the confused person in search of himself when the other denies it and crushes his humanity .by tracks the rhythmic sound streams that expresses the poet s psyche and it interacts with the structure of the poem to produce meaning .The poem is a structure formed by words and by tones as well and they combine together to express the poetic and emotional experience of the poet.